(3GdecGf aj CYeGd Ydj HOQ GdQhGFjI (B: s (3OQGSI JMdjdjI (B/ s - (3NjQjI SYOj cQjes; (3NjQj OheI (B: s; (3SdjeGf YHOGdYXje GdYWGQ (B: s ((3GdbGgQI (B: s (3NjQjI SYOj cQje (B: s, 2014)
(3GYJeO GdHMK Ydi GdefgL GdJMdjdj hGSJaGO ef OQGSGJ Yde GdSQO HhLg YGe(B: (3ceG GSJNOeJ GGdefgL GdHfjhj (B( (3GdKfGFjGJ GdeJVGOI(B) (3Ke GdefgL GdSejhdhLj hcPdc efgL GdfbO GdKbGaj(B. (3LGAJ GdOQGSI aj ebOeI hJegjO hKdGKI aUhd Je aj GdJegjO GdJYQja HGdcGJH Ydj HOQ hCge CYeGdg hef Ke GdJWQb deaghe GdecGf(B: (3GdaUd GdChd LGA HYfhGf GdecGf Ydi VhA Hfjhj SejhdhLj (B: (3LGA GdeHMK GdChd HYfhGf KfGFjI GdecGf(B: (3hGdeHMK GdKGfj HYfhGf SjejhdhLjI GdecGf(B: (3CeG GdaUd GdKGfj LGA HYfhGf GdYdGbI Hjf GdecGf hGdYfGUQ GdSQOjI GTJed Ydi eHMKjf JfGhd GdeHMK GdChd YdGbI GdTNUjI HGdecGf(B: (3haj GdeHMK GdKGfj JfGhd YdGbI GdecGf Hcd ef GdRef hGdMOK(B: (3CeG GdaUd GdKGdK abO Ted YdGbI GdecGf HGdefXheI GdKbGajI(B: (3JfGhd GdeHMK GdChd YdGbI GdecGf HKbGaI GdCaQGO CeG GdeHMK GdKGfj abO JfGhd GdLOd Hjf GdecGf hGdXhGgQ GdGLJeGYjI(B: (3hGdeHMK GdKGdK JWQb Edi YdGbI GdecGf HGddZI GdQhGFjI(B. (3hCeG GdNGJeI aPcQ ajgG CHQR GdfbGW GdegeI GdJj JhUdJ EdjgG GdOQGSIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI h COGHgGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdQhGjIs; (3GdSjejhdhLjIs; (3GdecGfs